2009
DOI: 10.1210/jc.2008-2333
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Regulatory Subunit Type 1A of Cyclic Adenosine 5′-Monophosphate-Dependent Protein Kinase (PRKAR1A): Phenotype Analysis in 353 Patients and 80 Different Genotypes

Abstract: CNC is genetically and clinically heterogeneous. Certain tumors are more frequent, with specific mutations providing some genotype-phenotype correlation for PRKAR1A mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
466
2
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 398 publications
(484 citation statements)
references
References 36 publications
6
466
2
10
Order By: Relevance
“…In a mouse model of inherited tumour syndrome Carney complex (CNC) with defect in the regulatory subunit 1a of PKA, there is evidence that prkar1a þ / À (regulatory subunit 1a of PKA) mice developed HCC, while the PKA activity in these mice remained unchanged 47 . However, in another study, CNC patients with prkar1a mutations have been shown to develop a spectrum of carcinomas but not HCC 48 . These reported studies reveal an opposing role of cAMP/PKA pathway in different cellular contexts.…”
Section: Discussionmentioning
confidence: 91%
“…In a mouse model of inherited tumour syndrome Carney complex (CNC) with defect in the regulatory subunit 1a of PKA, there is evidence that prkar1a þ / À (regulatory subunit 1a of PKA) mice developed HCC, while the PKA activity in these mice remained unchanged 47 . However, in another study, CNC patients with prkar1a mutations have been shown to develop a spectrum of carcinomas but not HCC 48 . These reported studies reveal an opposing role of cAMP/PKA pathway in different cellular contexts.…”
Section: Discussionmentioning
confidence: 91%
“…At least 50% of individuals with isolated primary pigmented nodular adrenocortical disease have a PRKAR1A mutation. [18][19][20] Thus, isolated primary pigmented nodular adrenocortical disease is sufficient for referral to genetic consultation. PRKAR1A mutations are found in 71% of individuals with at least two major diagnostic criteria for Carney complex 18 ( Table 3).…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…CNC is a rare endocrine multi-organ syndrome previously diagnosed in ~750 patients (6). A mutation in the PRKAR1A gene has been identified in more than 70% of the cases, including 80% of those with PPNAD (7,10). PRKAR1A is located at the 17q 24.2-24.3 locus and is composed of 11 exons (6).…”
Section: Discussionmentioning
confidence: 99%